Incidence and characteristics of patients presenting with acute myocardial infarction and non‐obstructive coronary artery disease. Issue 1 (23rd June 2015) - Najib, Khalid; Boateng, Stephen; Sangodkar, Sandeep; Mahmood, Shad; Whitney, Hannah; Wang, Chihsiung E.; Racsa, Patrick; Sanborn, Timothy A.
Abstract : Objectives: This study aimed to characterize the etiologies of patients presenting with myocardial infarction (MI) and found to have non‐obstructive coronary artery disease (NOCAD) and compare risk factors and in‐hospital mortality to those with obstructive coronary artery disease (CAD). Background: Patients presenting with an MI are often found to have NOCAD defined as less than 50% luminal diameter reduction by visual estimation on coronary angiography. Methods: This study is a retrospective analysis of a total of 2, 038 patients that presented to NorthShore University HealthSystem with MI and underwent coronary angiography from 2010 to 2013. Results: 1, 822 patients (89%) had CAD and 216 (11%) had NOCAD. Of the NOCAD patients, the most common etiologies were Takotsubo cardiomyopathy (28%), no alternative explanation (26%), demand ischemia (21%), myopericarditis (7%), coronary artery vasospasm (5%), and coronary artery dissection (3%). NOCAD patients were more likely to be younger and female. There was no significant difference between NOCAD and CAD patients in terms of in‐hospital mortality (3.7% vs. 4.0% respectively, OR = 1.1, 95% CI 0.5–2.3, P  = 0.83 by univariate logistic regression, OR = 1.2, 95% CI 0.5–3.1, P  = 0.74 by multivariable analysis). Conclusions: CAD patients were more likely to have traditional risk factors of diabetes, hypertension, hypercholesterolemia, previous MI, previous revascularization with percutaneous coronary intervention or coronary artery bypass graft surgery. Patients presenting with MI and NOCAD were found to have several different etiologies on coronary angiography with the most common being Takotsubo cardiomyopathy. © 2015 Wiley Periodicals, Inc.